Conceptualization of the Notion “Musical Project of Academic Art” - Obukh, Liudmyla (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2019)
The relevance of the issue of mastering technology management fundamentals involves the use of the musical project as a promotional product in the realities of the modern economic world. The scientific novelty of the research lies in the attempt to single out and specify the theoretical aspects of projecting in academic music art. It is the first research to deal with the concept of ‘music project’ in academic music art and to suggest its definition. The research is aimed at the conceptualization of the notion of «musical project of academic art», its interpretation in the context of development of academic music art management. The methodology of the research is characterized by a complex combination of a number of interdisciplinary theoretical approaches and scientific principles of systematization and generalization of the researched issue, which made it possible to identify the meaning content and range of the notion of “project” in a scientific discourse. The findings and conclusions. So, summarizing theoretical developments, we propose author’s definition of the concept of «musical project of academic art»: it is a unique step-by-step organization of resonance events of academic musical art on a national or local scale as a form of communication program in the process of management and as a type of communication program in the system of strategic process of functional management in order to attract it as a mechanism of positive social action. The classification of a musical project of academic art according to the following criteria is offered: by concept (commercial, socially-oriented, educational), volume (widescale and chamber) and perspective (formation of a new listening audience and expansion of the fan-music zone). Musical, like any other artistic project, involves the use of products of socio-cultural activity and the involvement of appropriate universal techniques (Event management, PR-service), which contribute to effective management. The significant signs of a musical project of academic art: actuality, which depends on socio-cultural conditions and can be dictated by these conditions, and independently dictate the favorable conditions of society and acts as a consolidating and motivational force of all components of the project; motivation, which is dictated by the personal goals of managers and executors (social significance, professional competence, and, as a consequence, the desired reward); talent of contractors, managers, as a guarantee of the success of the project, determines its quality and makes it possible to compete in the socio-cultural market. All of these criteria and characteristics of the music project are interrelated and complementary, convincing that the field of academic art in the Ukrainian socio-cultural space can produce a positive cultural image of the state in the world civilization arena. Prospects for further explorations relate to music management in contemporary Ukraine, peculiarities of its formation and development, revealing the institutional structure of academic music management, expressing the role of personality and so on.